Outstanding Marine Molecules 2014
DOI: 10.1002/9783527681501.ch13
|View full text |Cite
|
Sign up to set email alerts
|

Marine Peptide Secondary Metabolites

Abstract: A large pro port ion of the marine natural produc ts actu ally u n der clinical inve stigat ion are pept ide sec ondary metabolites with unusual amino acids re sidues. This growing f amily of compounds can be produced via tw o major p athw ays, r ibosomal and nonribosomal. In this c hapt er a re p re sent ed a nd illu strated, with a fe w f amou s examples, ribosomal-and n onribosomal-d erived pe ptides. Atte ntion is focused on fi ve families of biological ly a ctive marine p eptides of d iverse origin, rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 254 publications
0
14
0
Order By: Relevance
“…Laxaphycins are cyclic lipopeptides synthesized through a hybrid PKS/NRPS biosynthetic pathway by different marine or freshwater cyanobacteria. They contain amino acids of alternate stereochemistry ( l or d ) and feature a rare fatty β-amino acid with a linear chain of up to 12 carbons [ 7 ]. Several studies have reported structural variants and likely biosynthetic derivatives of laxaphycins that can be separated into two groups, the laxaphycin A-type peptides, whichare cyclic undecapeptides, and the laxaphycin B-type peptides, which are cyclic dodecapeptides.…”
Section: Introductionmentioning
confidence: 99%
“…Laxaphycins are cyclic lipopeptides synthesized through a hybrid PKS/NRPS biosynthetic pathway by different marine or freshwater cyanobacteria. They contain amino acids of alternate stereochemistry ( l or d ) and feature a rare fatty β-amino acid with a linear chain of up to 12 carbons [ 7 ]. Several studies have reported structural variants and likely biosynthetic derivatives of laxaphycins that can be separated into two groups, the laxaphycin A-type peptides, whichare cyclic undecapeptides, and the laxaphycin B-type peptides, which are cyclic dodecapeptides.…”
Section: Introductionmentioning
confidence: 99%
“…The figure suggests a Ser in position 2, a Hyp in position 4, a Hse in position 5, and a d -Tyr in position 6 while the text indicates a Hse, Pro, Ser, and d -Tyr in these respective positions. These slight differences in position and stereochemistry show the complexity that chemists face in confirming structures of natural products [ 9 ].…”
Section: Discovery and Characterization Of Laxaphycins And Their Derivativesmentioning
confidence: 99%
“…Dehydroamino acids are commonly found in cyanobacterial peptides [ 9 ] and more generally in peptides of microbial origin [ 70 ]. Several studies have shown that these amino acids can structure peptides, similarly to 2-aminoisobutyric acid (Aib) [ 71 , 72 ].…”
Section: Chemical Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these peptides have been selected by evolution in both freshwater and oceanic cyanobacteria and may confer to them an ecological advantage. Laxaphycins are divided in two sub-families: laxaphycin A-type, undecapeptides with a segregation of hydrophobic and hydrophilic residues; and laxaphycin B-type, dodecapeptides in which hydrophobic and hydrophilic residues are alternated [ 8 ]. Laxaphycin B-type members such as laxaphycins B, B2 and B3 have presented antifungal, antimicrobial and cytotoxic activities [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%